Nuclear cyclin D1: An oncogenic driver in human cancer - Kim, Jong Kyong (2009)
Perturbations in the regulation of the core cell cycle machinery are frequently observed in human cancers. Cyclin D1 which functions as a mitogenic sensor and allosteric activator of CDK4/6, is one of the more frequently altered cell cycle regulators in cancers. Cyclin D1 is frequently overexpressed in cancers and its overexpression can be attributed to many factors including increased transcription, translation, and protein stability. Although cyclin D1 overexpression is clearly implicated in the affected cancers, overexpression of cyclin D1 is not sufficient to drive oncogenic transformation. Rather, emerging evidence suggests that nuclear retention of cyclin D1 resulting from altered nuclear trafficking and proteolysis is critical for the manifestation of its oncogenicity. This review provides a brief overview of current data documenting various mechanisms underlying aberrant cyclin D1 regulation in human cancers and their impact on neoplastic transformation.